2017
DOI: 10.3892/mmr.2017.6194
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic genes in kidney renal clear cell carcinoma by RNA-seq data analysis

Abstract: The present study aimed to analyze RNA-seq data of kidney renal clear cell carcinoma (KIRC) to identify prognostic genes. RNA-seq data were downloaded from The Cancer Genome Atlas. Feature genes with a coefficient of variation (CV) >0.5 were selected using the genefilter package in R. Gene co-expression networks were constructed with the WGCNA package. Cox regression analysis was performed using the survive package. Furthermore, a functional enrichment analysis was conducted using Database for Annotation, Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…CDCA8 is related to the distant metastasis risk of breast cancer [51,52]. With regard to renal cancer, CDCA8 has also certain prognostic value [53]. CDCA8 promotes the malignant progression of cutaneous melanoma [54].…”
Section: Discussionmentioning
confidence: 99%
“…CDCA8 is related to the distant metastasis risk of breast cancer [51,52]. With regard to renal cancer, CDCA8 has also certain prognostic value [53]. CDCA8 promotes the malignant progression of cutaneous melanoma [54].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that inactivation of CLDN11 could promote cell migration in nasopharyngeal carcinoma (Li et al, 2018). KIF4A were identified as prognostic gene or key gene involved in the metastasis of renal cell carcinoma in recent survey (Gu et al, 2017;Wei et al, 2019). Anticancer Patients with papillary renal cell carcinoma (pRCC) were divided into low-and high-risk subgroups based on the median value of the risk score calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Human cell division cycle associated 8 (CDCA8) was another hub gene among the overlapping DEGs. As a chromosomal passenger complex component [44], CDCA8 upregulation is related to the carcinogenesis of a variety of tumors [45,46]. CDCA8 has been proven to be a tumor promoter that is overexpressed in various kinds of tumors and is essential for cancer cell survival and malignancy [47].…”
Section: Discussionmentioning
confidence: 99%